2014
DOI: 10.3109/14767058.2014.914489
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat maternal diet decreases adiponectin receptor-1 expression in offspring

Abstract: In early life, over-nutrition may increase the risk of insulin resistance in the adult stage. Adiponectin and its receptor may play a key role in this process. This study aimed to identify the effect of a high-fat (HF) maternal diet on metabolic parameters and muscle adiponectin signaling in young adult offspring. We found that offspring born to dams fed HF chow (HF; 31% of calories from fat) had elevated body and adipose tissue weight and higher serum glucose levels after glucose challenge at three weeks (W3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…99 SDM na 63YASBPZaborska K.E. 101 SDM na na YAFAT, INSHou M.SDM na 56PPPFAT, GLU, INS, TGSome studies appear more than one time with different sex, age stage or timing of the intervention. Some of the studies reported more than one experiment and therefore sometimes more than one experimental group could be identified for the purposes of our analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…99 SDM na 63YASBPZaborska K.E. 101 SDM na na YAFAT, INSHou M.SDM na 56PPPFAT, GLU, INS, TGSome studies appear more than one time with different sex, age stage or timing of the intervention. Some of the studies reported more than one experiment and therefore sometimes more than one experimental group could be identified for the purposes of our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The initial screen was based on the paper’s title, abstract and occasional whole-text scan and then after in-depth screening, 203 relevant citations remained for further review. Finally, 68 citations were used in meta-analysis 1317, 1921, 23, 26, 38, 43, 44, 47101 . The 135 excluded studies with the reasons for their exclusion are available in Supplementary Table S6.
Figure 10PRISMA flow chart summarizing study selection processes.
…”
Section: Methodsmentioning
confidence: 99%
“…Offspring of mothers fed high-fat diets grew to be significantly heavier and had significantly elevated fasting glucose levels compared to mice exposed to a normal maternal diet. 33 Given that ADIPOQ helps to maintain insulin sensitivity and ADIPOQ levels are inversely correlated with obesity, the results of this study suggest that metabolic disturbances in response to maternal high-fat diet may also be mediated by ADIPOQ. 33 …”
Section: Maternal and Early Postnatal Dietmentioning
confidence: 72%
“… 33 Given that ADIPOQ helps to maintain insulin sensitivity and ADIPOQ levels are inversely correlated with obesity, the results of this study suggest that metabolic disturbances in response to maternal high-fat diet may also be mediated by ADIPOQ. 33 …”
Section: Maternal and Early Postnatal Dietmentioning
confidence: 72%
“…Дети матерей, употреблявших большое количество жиров во время беременности, склонны к набору лишнего веса. Считается, что в этом случае дефицит адипонектина (гормона, ответственного за чувствительность к инсулину) является фактором, инициирующим эпигенетические модификации [33]. Диета с высоким содержанием жиров во время беременности инициирует недостаточную сосудорасширяющую реакцию на ацетилхолин у потомства.…”
unclassified